Pilot-scale experimental evaluation of induction melting of Ti-46Al-8Nb alloy in the fused BaZrO3 crucible. (January 2019) - Chen, Guangyao; Lan, Baobao; Xiong, Fuhao; Gao, Pengyue; Zhang, Hao; Lu, Xionggang; Li, Chonghe
Abstract: Vacuum induction melting in the refractory crucible has been considered as a cost reduction way for the fabrication of TiAl-based alloys. In this study, experimental proof for the feasibility of the pilot-scale melting of Ti-46Al-8Nb alloy was performed in the fused BaZrO3 crucible. Results revealed that the obtained Ti-46 at% Al-8 at% Nb ingot had the oxygen concentration of 0.078 wt%, which was lower than the permitted oxygen concentration (0.1 wt%) of the high-performance TiAl-based alloy. According to the thermodynamic analysis, the oxygen contamination of Ti-46Al-8Nb ingot by the crucible refractory was attributed to the dissolution of BaZrO3 and ZrO2 refractory. Meanwhile, a good macroscopic and microcosmic homogeneity of the Ti-46Al-8Nb ingot was achieved with the refinement time during the melting at 1550 °C for 30s, and the microstructure of Ti-46Al-8Nb alloy was largely composed of lamellar α2 +γ with different orientations and small amount of bulk γ phase. Preliminary results confirmed that the fused BaZrO3 can be considered as an appropriate refractory for the melting of TiAl-based alloys. Highlights: The Ti-46Al-8Nb alloy was fabricated in fused BaZrO3 crucible using vacuum induction melting. A low oxygen concentration (0.078wt%) of the alloy was obtained, the oxygen concentration of this ingot met the requirement of high performance of TiAl-based alloy, which satisfy the 0.1 wt% oxygen concentration. Dissolution of BaZrO3 and ZrO2 was responsible for the oxygen contamination of the Ti-46Al-8Nb ingot.